Death from pan-resistant superbug - Larry Nichols (University of São Paulo, 2019)
Acinetobacter baumannii has emerged as a pan-resistant superbug causing fatal infections in vulnerable patients. This report is the case of an immunosuppressed transplant patient with a fatal pneumonia due to pan-resistant Acinetobacter baumannii. Alternative therapy for resistant Acinetobacter infection is currently the subject of intense interest and research. This report illustrates the features of this type of emerging infectious disease and reviews some of the novel approaches to treatment.